How new quality productivity drives china’s sustainable development: Evidence from dynamic indicator evolution - Minhua Lu (PLoS ONE, 2025)
New Quality Productivity (NPQ) plays a pivotal role in driving China’s transition toward sustainable economic development. This study constructs a multidimensional evaluation framework incorporating thirteen indicators across digitalization, green development, and institutional innovation, and utilizes entropy-based analysis of China’s time-series data from 2000 to 2022. The results reveal that NPQ markedly enhances economic efficiency, social inclusiveness, and environmental sustainability through technological progress, optimization of resource allocation, and institutional improvement. The composite index rose sharply from 0.0598 in 2000 to 0.9627 in 2022, representing an average annual growth rate of 12.4%. Weight analyses identify low-carbon technology innovation, digital accessibility, and environmental policy strictness as core drivers, with significant structural advances corresponding to major policy initiatives in 2012, 2016, and 2020. Robustness and statistical tests confirm the reliability of the model and the progressive strengthening of digitalization and green development dimensions over time. This study provides empirical evidence to guide NPQ-related policy formulation and contributes new theoretical perspectives to global sustainable development discourse by highlighting the importance of coordinated technological, environmental, and institutional advancement.